Ectopic expression of a maize calreticulin mitigates calcium deficiency-like disorders in sCAX1-expressing tobacco and tomato - Wu, Qingyu; Shigaki, Toshiro; Han, Jeung-Sul; Kim, Chang Kil; Hirschi, Kendal D.; Park, Sunghun (My University, 2013)
Deregulated expression of an Arabidopsis H[superscript +]/Ca[superscript 2+] antiporter (sCAX1) in agricultural crops increases total calcium (Ca[superscript 2+]) but may result in yield losses due to Ca[superscript 2+] deficiency-like symptoms. Here we demonstrate that co-expression of a maize calreticulin (CRT, a Ca[superscript 2+] binding protein located at endoplasmic reticulum) in sCAX1-expressing tobacco and tomato plants mitigated these adverse effects while maintaining enhanced Ca[superscript 2+] content. Co-expression of CRT and sCAX1 could alleviate the hypersensitivity to ion imbalance in tobacco plants. Furthermore, blossom-end rot (BER) in tomato may be linked to changes in CAX activity and enhanced CRT expression mitigated BER in sCAX1 expressing lines. These findings suggest that co-expressing Ca[superscript 2+] transporters and binding proteins at different intracellular compartments can alter the content and distribution of Ca[superscript 2+] within the plant matrix.
Keywords: Calcium; CAX; CRT; Co-expression; Tomato